The Pictorial Mode : Space and Time in the Art of Bryant, Irving, and Cooper - Ringe, Donald A. (Book collections on Project MUSE., 1971)
Focusing on style as a means of thematic expression, Donald A. Ringe in this study examines in detail the affinities that exist between the paintings of the Hudson River school and the works of William Cullen Bryant, Washington Irving, and James Fenimore Cooper.